Children's 1000 world picture dictionary - Kamran, Sumera (Children Publication Karachi, 2004)
The *Children's 1000-Word Picture Dictionary* is a visual learning tool designed to help young children build their vocabulary. It features 1,000 common words, each accompanied by colorful illustrations for easy understanding. The dictionary covers a wide range of topics, from animals and objects to actions and emotions. Its engaging format makes learning fun and accessible for early learners, enhancing language development.